Impact of retailer's deployment of mobile technology on supply chain integration in Osogbo, Nigeria. - Ojo, Aderonke Julian; Ajayi, Adeyinka Peter (Corpus Intellectual, 2024)
This research assessed the effect of retailers' deployment of mobile technology (mobile telephony, social media, and digital payment platforms) on supply chain integration (SCI) in Osogbo Metropolis, Nigeria. A quantitative method was adopted for this study. The impact of retailer's deployment of mobile telephony, social media, and digital payment platforms on supply chain integration (SCI) in Osogbo Metropolis, Nigeria, was analysed using Partial Least Squares SEM (PLS-SEM) with the aid of the SmartPLS-3 software SEM. According to the R-squared value of 0.571, the construct variables (DPP, MT, and SM) collectively account for 57.1 per cent of the variation observed in the exploratory variable (SCI). Suggests a good model fit. The study results showed that FMCG retailers' adoption of mobile technology in the three areas of mobile telephony, digital payment platforms, and social media has no effect on the success of supply chain integration and does not considerably affect the achievement of supply chain integration. Keywords: supply chain integration, mobile telephony, digital payment platform, social media, fast-moving consumer goods, retailers.